2023
DOI: 10.1186/s12872-022-03030-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of 14 pediatric mycoplasma pneumoniae pneumonia associated thrombosis: a retrospective study

Abstract: Objective This study aimed to investigate the clinical characteristics and long-term prognosis of mycoplasma pneumoniae pneumonia (MPP)-associated thrombosis and to gain a better understanding of the diagnosis and treatment of the disease. Methods The medical records of 14 children with MPP-associated thrombosis between January 2016 and April 2020 were retrospectively reviewed at the Tianjin Children’s Hospital. Resul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…However, these manifestations may also be absent. 15–17 In our study, we observed that among the 16 children diagnosed with PE, 16 exhibited cough, 4 experienced hemoptysis, 4 reported shortness of breath, and 8 complained of chest pain. Additionally, some patients displayed no specific symptoms, a finding consistent with existing literature.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…However, these manifestations may also be absent. 15–17 In our study, we observed that among the 16 children diagnosed with PE, 16 exhibited cough, 4 experienced hemoptysis, 4 reported shortness of breath, and 8 complained of chest pain. Additionally, some patients displayed no specific symptoms, a finding consistent with existing literature.…”
Section: Discussionmentioning
confidence: 50%
“…Furthermore, MP infection can lead to hepatocyte damage, hypoxia, and immune-related injuries, potentially augmenting the synthesis of endogenous coagulation factors. Concurrently, there may be a reduction in the synthesis of critical anticoagulation factors like antithrombin III (AT-III), protein C, and protein S. 15 Cases involving elevated coagulation factors and anomalous anticoagulation proteins have also been documented in the context of MP infection coupled with embolism. 5 , 16 Notably, half of the pulmonary thrombosis patients developed on the same side as the pulmonary consolidation in our study, further supporting the hypothesis that isolated arterial thrombosis may be in situ thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…It releases toxins, causing endothelial damage and oxidative damage in the body, and releases inflammatory cytokines, such as TNF-α, IL-6, and IFN-gamma, causing endothelial dysfunction [7][8][9][10][11]. Second, M. pneumoniae antigen has common antigens with multiple organs of the human body, such as the heart, brain, and kidney, and it can produce autoantibodies and form immune complexes, resulting in the occurrence of a variety of extrapulmonary complications after infection [12,13]. What's more, vascular occlusion can cause blood flow obstruction due to vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…There are currently only a few cases of mycoplasma infection with intracardiac and cerebral thrombosis reported in the literature. Fu et al reported pulmonary in five cases, cerebral in two cases, pulmonary and cardiac in two cases, and lower extremity artery and cardiac thrombosis in one case [ 12 ]. Intracardiac thrombosis can be the only type of thrombosis present in a patient, and it can be asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals experiencing prolonged chest pain, palpitations, or episodes of fainting have sought medical attention. In some cases, comprehensive cardiac evaluations reveal no structural abnormalities or traditional risk factors [30]. These symptoms, which can be severely debilitating, underscore the need for a deeper understanding of COVID-19's impact on the heart and vascular system.…”
Section: Investigating Rare and Unusual Symptoms Reported In Post-cov...mentioning
confidence: 99%